(3aJM GdhgGH TQM efgL GdWdGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s
(3ChdgG (B:s
(3cJGH GdaQGFV Cj eSGFd bSeI GdehGQjKeY aQjVI HeYfi eaQhVI Cj ebOQI deG ajgG ef GdSgGe GdebOQIs
(3BNQgG (B:s
(3hHYOe JMQjegG Cf cGf SHHgG JQc CYeGd dGfgG bO JTb Ydjg hefg JQc Sbj GdCTLGQ GdeQghfI HJhGab GdYGbOjf aEfgGjR NdGaG ddQhjGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3cTa GdXfhf (B2 / 1875s
(3TPQGJ GdPgH (B8 / 134s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs